Heart rhythm in vitro: measuring stem cell-derived pacemaker cells on microelectrode arrays - Kussauer, Sophie; Dilk, Patrick; Elleisy, Moustafa; Michaelis, Claudia; Lichtwark, Sarina; Rimmbach, Christian; David, Robert; Jung, Julia (Frontiers in Cardiovascular Medicine, 2024)
Background Cardiac arrhythmias have markedly increased in recent decades, highlighting the urgent need for appropriate test systems to evaluate the efficacy and safety of new pharmaceuticals and the potential side effects of established drugs. Methods The Microelectrode Array (MEA) system may be a suitable option, as it provides both real-time and non-invasive monitoring of cellular networks of spontaneously active cells. However, there is currently no commercially available cell source to apply this technology in the context of the cardiac conduction system (CCS). In response to this problem, our group has previously developed a protocol for the generation of pure functional cardiac pacemaker cells from mouse embryonic stem cells (ESCs). In addition, we compared the hanging drop method, which was previously utilized, with spherical plate-derived embryoid bodies (EBs) and the pacemaker cells that are differentiated from these. Results We described the application of these pacemaker cells on the MEA platform, which required a number of crucial optimization steps in terms of coating, dissociation, and cell density. As a result, we were able to generate a monolayer of pure pacemaker cells on an MEA surface that is viable and electromechanically active for weeks. Furthermore, we introduced spherical plates as a convenient and scalable method to be applied for the production of induced sinoatrial bodies. Conclusion We provide a tool to transfer modeling and analysis of cardiac rhythm diseases to the cell culture dish. Our system allows answering CCS-related queries within a cellular network, both under baseline conditions and post-drug exposure in a reliable and affordable manner. Ultimately, our approach may provide valuable guidance not only for cardiac pacemaker cells but also for the generation of an MEA test platform using other sensitive non-proliferating cell types.